Adsorption of chromium(VI) by titanium(IV) oxide coated on a silica gel surface - Kubota, L. T.; Gushikem, Y.; Moreira, J. C. [UNESP] (Royal Soc Chemistry, 1991)
Titanium(IV) oxide, coated on the surface of silica gel (surface area, 308 m2 g-1; amount of Ti(IV) per gram of modified silica gel, 1.8 x 10(-3) mol), was used to adsorb CrO4(2-) ions from acidic solutions. The exchange capacity increased at lower pH values and was affected to some extent by the acid used. The material was used to preconcentrate Cr(VI) from 0.5 ppm solutions of chromate very efficiently and virtually 100% recovery was achieved in every instance.
Keywords: Titanium(IV) oxide modified silica; Silica gel surface coated with titanium(IV) oxide; Chromium(VI) determination; Preconcentration of chromium(VI)